A new genus and new species of leucosiid crab (Crustacea: Decapoda: Brachyura) from coral reefs in the Indo-West Pacific - Komai, Tomoyuki; Ng, Peter K. L. (Zootaxa, 2012)
A new genus and new species of leucosiid crab, Coralliocryptus caementa n. sp., is described from Indo-West Pacific coralreefs in the Ryukyu Islands (Japan), Vanuatu, and Comoros. Although the new genus exhibits superficial resemblance to theIphiculidae in having prominent vertical spiniform teeth on the cutting edges of the chela and the female abdomen consisting offreely articulated somites, the deeply excavated female sterno-abdominal cavity, which is completely covered by the abdomen,unambiguously places this unique taxon in the Leucosiidae. The highly eroded, coral-rubble mimic carapace suggests somedegree of relationship between Coralliocryptus and some other ebaliinine genera, e.g., Alox Tan & Ng, 1995, Oreophorus Rüppel, 1830, Oreotlos Ihle, 1918.Key words: Crustacea, Decapoda, Brachyura, Leucosiidae, new genus, new species, Indo-West Pacific